FEATURES OF CLINICAL PRESENTATION, DIAGNOSIS, AND PREVENTION OF HIV INFECTION AMONG THE GENERAL POPULATION AND MILITARY PERSONNEL UNDER WAR CONDITIONS - Klymenko, Nataliya; Borshchenko, Valeriia; Svitailo, Vladyslav; Chemych, Oksana; Saienko, Olexandr; Chemych, Mykola (Eastern Ukrainian Medical Journal, 2026)
Relevance. Timely detection of HIV infection remains a key factor in reducing incidence and preventing transmission. In the military context, this means combining screening at mobilization, periodic testing for individuals at increased risk, and testing in case of characteristic symptoms or after high-risk exposures. Since the beginning of the full-scale Russian invasion of Ukraine, the displacement of large numbers of people has caused problems with treatment and prevention, which may have led to the spread of infection to new regions. Military personnel and veterans may face increased risks of infection due to combat injuries, specific features of medical support in field conditions, and challenges in ensuring confidentiality and continuity of antiretroviral therapy (ART) during rotations and combat operations.Objective. To summarize current clinical, epidemiological, and diagnostic features of HIV infection and existing and prospective prevention measures among the general population and military personnel under wartime conditions, as well as to identify key directions for improving diagnosis, treatment, and prevention.Materials and Methods. A systematic analysis of scientific publications, official reports, and recommendations from international organizations (EUCALB, CDC, ECDC) from 2013 to 2025 was conducted. Both original studies and systematic reviews and meta-analyses were analyzed.Results. Practical recommendations for military medical services should include HIV testing within routine examinations using “opt-out” algorithms to reduce stigma. Rapid linkage to care for positive cases should be ensured - initiation of etiotropic therapy and virological assessment (CD4 count and viral load) immediately after confirmation. The expansion of rapid test (RDT) use in standard protocols during mobilization and in field medicine is justified. Implementation of self-testing algorithms, use of dried blood spot (DBS) methods, and point-of-care (POC) platforms for rapid diagnostics directly at the patient is recommended, which is critically important in areas with disrupted infrastructure. This approach reduces decision-making time and ensures patient routing in case of a positive result.Conclusions. It has been demonstrated that adapting HIV response systems to wartime conditions requires decentralization of diagnostics through the implementation of the “opt-out” model, use of rapid tests, and deployment of POC platforms in field conditions. The expansion of access to biomedical prevention post-exposure prophylaxis(PEP)/pre-exposure prophylaxis (PrEP), with priority for long-acting injectable forms, is justified. Implementation of the proposed organizational and technological solutions will ensure confidentiality, continuity of treatment, and preservation of operational readiness of personnel during prolonged martial law.